Rescuing the negative effects of aging in burn wounds using tacrolimus applied via microcapillary hydrogel dressing. Issue 8 (December 2022) - White-Dzuro, Colin G.; Pollins, Alonda C.; Kalmar, Christopher L.; Assi, Patrick E.; Rector, John A.; Bellan, Leon M.; Thayer, Wesley P.
Highlights: Early conversion of partial to full thickness burns is a major cause of morbidity. The pathogenesis is not well understood, but overactive immune response thought to play a role. Tacrolimus immunotherapy prevents burn conversion in a murine model and rescues the negative healing phenotype seen in aging. Future studies will look at other inflammatory mediators including similar inflammatory cytokines and macrophages. Abstract: Introduction: Delays in treatment of burn injuries can lead to significant morbidity, loss of function, and poor aesthetic appearance. Preventing conversion from partial- to full-thickness burns may help mitigate these sequelae. The pathophysiology of burn wound conversion remains unknown, but an overactive immune response is thought to be implicated. The purpose of this study was to determine whether downregulating the immune response via tacrolimus can decrease burn wound conversion. Methods: Assembly of the microfluidic hydrogels was achieved by embedding microfibers within a hydrogel scaffold composed of a gelatin-alginate blend. Tacrolimus stock solution for intraperitoneal injection was made by re-suspending powdered tacrolimus in DMSO at 10 mg/mL. 24 young (2–4 months) and 24 old (>16 months) mice were given partial thickness burns. The treatment cohort received either tacrolimus ointment with a hydrogel dressing (6 young and 6 old) or an intraperitoneal injection of a tacrolimus solution (6 young and 6 old), while the control cohort only received either only the microcapillary hydrogel dressing or an intraperitoneal injection of saline. Mice were euthanized at day 3 after injury and skin samples were taken. Burn depth was evaluated using Vimentin immunostaining. Results: In old mice, intraperitoneal injection of tacrolimus was able to significantly reduce burn wound depth compared to intraperitoneal injection of saline (p = 0.011). Similarly in old mice, topical hydrogel with tacrolimus was able to significantly reduce burn wound depth compared to hydrogel alone (p < 0.001). Topical hydrogel with tacrolimus was able to mitigate the detrimental effects of older age on wound conversion, such that burn wounds of older mice treated with tacrolimus hydrogel dressing had similar burn depths as younger mice (p = 0.240). Conclusions: Utilizing a combination treatment of tacrolimus and microcapillary hydrogel is able to rescue the negative effects of aging and prevent partial- to full-thickness burn wound conversion. Hopefully these findings will encourage deeper investigation into the possible therapeutic advantages of utilizing immunosuppressive agents to decrease morbidity after burn injuries. Future research will need to specifically investigate IL-2 as an inhibitory target in the acute inflammatory cascade of burn injury.